The Re-evaluation of the Kocain (Antalya) Eirenarches, Anteirenarches and Diogmites Inscriptions - (:unkn) unknown (KOC UNIV SUNA & INAN KIRAC RES CTR MEDITERRANEAN CIVILIZATIONS-AKMED, 2015)
In 1926 the Italian scholar G. Moretti published a total of 28 inscriptions which he discovered in 1919 in the Kocain Cave on Hisardag / Indagi on the way to the village of Ahirtas in the province of Antalya. These inscriptions are dedications by eirenarches, anteirenarches and diogmites. However, our studies on these inscriptions have shown that many were published in an incomplete or faulty manner. The Kocain Cave is located on Hisardagi / Indagi at an altitude of 1171 m. about 45 km. north of Antalya. The cave comprises a grand hall, which is 600 m. long, only 35 m. wide at the mouth, 75 m. wide inside, and its ceiling reaches a ceiling of 50-60 m. in places. It was registered as a first-degree archaeological / natural site. The cave houses a large cistern from the Roman period. In front of the cave are the remains of a building complex dated to the Roman Imperial period (?). Inside the cave near the mouth is a mass of limestone rock with a suitable surface engraved with inscriptions containing the names of numerous eirenarches, anteirenarches and their assistants diogmites. Probably due to the risks related to their duties, these enforcement officers made votive offerings here. Rereading the inscriptions allows us to state the following tentatively: 1) Kocain Cave was not a cult area for Meter Oreia. 2) Contrary to what is known to date, no ethnic of any eirenarches, anteirenarches or any other person is mentioned in the inscriptions. Therefore, the enforcement officers who made offerings here could have come from only one city. 3) Some officers were both eirenarches and anteirenarches, probably starting the position as an anteirenarches and finishing as an eirenarches. 4) As inferred from the inscriptions, sometimes the diogmites also acted as anteirenarches. This is important for recording for the first time a diogmites acting in place of anteirenarches. 5) Some eirenarches or anteirenarches made the offerings together with the diogmites under their command. This can be explained as either the definition of their duties was altered or the officers under their command changed. 6) Only one officer has the gens name Aurelius; none other has. This suggests that the inscriptions should be dated before A.D. 212. As known, banditry increased in Asia Minor after the mid-2nd century; therefore the cities of Asia Minor would have taken security measures. Therefore, eirenarches and other militia of the cities in Pamphylia and Pisidia would have functioned from a position of strength in the mid-2nd century A.D.